(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
With the aim of contributing to a paradigm shift from domination to harmony in the relationship between <<human beings>>, <<society>>, and <<non-human nature>>, this study highlights the potential to preserve and promote Heritage conservation through an environmental education strategy. This strategy includes transformative actions in the environment coordinated through museums, which serve as educational agencies of territorial significance and actively involve the community as a central and decisive participant. The strengths and potential of these institutions to protect heritage and strengthen local identity are illustrated through the Provincial Heritage and Environment Program. Projects such as the creation of the Rainbow Groups movement, the Rainbow Routes initiative, Green Map, and Overcoming, among others, together with workshops, events, lectures, competitions, clean-up campaigns, and numerous other activities carried out by eighteen municipal and specialized museums, showcase the results achieved with and within the community. These projects also provide insights into experiences implemented since 2006. Collectively, they have contributed to raising environmental and heritage awareness across the region. Over 350,000 individuals from all municipalities in the capital have participated in the diverse activities with social and cultural impact over the past fifteen years. The comprehensive, diverse, and widely participatory approach to environmental action represents an innovative model within the Heritage system, both for this province and the country as a whole. This Program has earned various national and international recognitions and awards.